Strategies For Improving Teacher Performance Through Strengthening Personality And Trust In Private Junior High School Teachers In Eastern Bogor Regency: Empirical Study Using Quantitative Approach with Path Analysis and SITOREM Techniques - Ila Nafilah; Rita Retnowati; Widodo Sunaryo (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study investigates strategies for improving teacher performance through strengthening personality and trust among private junior high school teachers in Eastern Bogor Regency using an empirical quantitative approach. A survey design was employed involving teachers from accredited private schools, with data collected through structured questionnaires and analyzed using path analysis to examine causal relationships among variables. The results indicate that personality exerts both direct and indirect influences on teacher performance, with trust functioning as a significant mediating variable that enhances relational and organizational effectiveness. The integration of SITOREM analysis provides a strategic framework for identifying priority areas of intervention based on indicator optimization and practical relevance. The findings highlight that performance improvement is not solely dependent on individual competence but also on the quality of interpersonal trust within institutional settings. The study contributes to educational management by offering an evidence based model that connects causal analysis with strategic decision making. These results provide practical implications for school leaders in designing targeted development programs that strengthen teacher capacity and organizational performance.